2008
DOI: 10.1055/s-0030-1247830
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Based Outcomes in Patellofemoral Arthroplasty

Abstract: This retrospective study evaluated the short-term functional outcome of patellofemoral arthroplasty using patient-based outcome measures. The study cohort included 17 patients who underwent patellofemoral arthroplasty (14 unilateral and 3 bilateral) between 1996 and 2005. Mean patient age was 56 years (range, 43-65 years), and mean follow-up was 52.5 months (range, 24-84 months). Clinical and radiographic assessment was performed using the Hospital for Special Surgery (HSS) knee score. Functional assessment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…After removing of duplicates and reviewing title, abstract and full text of the articles, a total of 57 cohort studies [1–3, 6, 7, 10, 11, 13, 15–20, 22, 24, 25, 30–34, 37–40, 45, 47, 50, 51, 55, 57, 58, 63–68, 70, 71, 73, 75, 84, 88–90, 92–96, 98, 99, 102–104] and three registries [4, 9, 72] were included in this study (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing of duplicates and reviewing title, abstract and full text of the articles, a total of 57 cohort studies [1–3, 6, 7, 10, 11, 13, 15–20, 22, 24, 25, 30–34, 37–40, 45, 47, 50, 51, 55, 57, 58, 63–68, 70, 71, 73, 75, 84, 88–90, 92–96, 98, 99, 102–104] and three registries [4, 9, 72] were included in this study (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies were level II prospective studies [1, 3, 7, 22, 38, 55, 63, 68, 73, 90, 92, 102], while 45 studies were level III retrospective studies or level IV case series [2, 6, 10, 11, 13, 15–20, 24, 25, 30–34, 37, 39, 40, 45, 47, 50, 51, 57, 58, 64–67, 70, 71, 75, 84, 88, 89, 93–96, 98, 99, 103, 104]. No level I studies were identified, and none of the studies were blinded or randomized.…”
Section: Resultsmentioning
confidence: 99%